2000
DOI: 10.1103/physrevb.61.14686
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic behavior of a mixed Ising ferrimagnetic model in an oscillating magnetic field

Abstract: The magnetic behavior of a mixed Ising ferrimagnetic system on a square lattice, in which the two interpenetrating square sublattices have spins σ (±1/2) and spins S (±1, 0), in the presence of an oscillating magnetic field has been studied with Monte Carlo techniques. The model includes nearest and next-nearest neighbor interactions, a crystal field and the oscillating external field. By studying the hysteretic response of this model to an oscillating field we found that it qualitatively reproduces the increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 34 publications
0
17
0
2
Order By: Relevance
“…Ferrimagnetic materials have, under certain conditions, a compensation temperature at which the resultant magnetization vanishes below its critical temperature 1 . Recently, it has been both experimentally and theoretically shown that the coercive field exhibits a rapid increase at the compensation point 2,3 . It is obvious that such kind of point has a technological importance 4,5 , because at this point only a small driving field is required to change the sign of the resultant magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrimagnetic materials have, under certain conditions, a compensation temperature at which the resultant magnetization vanishes below its critical temperature 1 . Recently, it has been both experimentally and theoretically shown that the coercive field exhibits a rapid increase at the compensation point 2,3 . It is obvious that such kind of point has a technological importance 4,5 , because at this point only a small driving field is required to change the sign of the resultant magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…This nonequilibrium phase transition was first observed in numerical solutions of mean-field equations of motion for ferromagnets in oscillating fields [63,64]. Subsequently it has been observed in numerous Monte Carlo simulations of kinetic Ising systems [56,65,66,67,68,69,70,71,72,73,74,75] and in further mean-field studies [68,70,71,73,76]. It may also have been experimentally observed in ultrathin films of Co on Cu(100) [58,77].…”
Section: Dynamic Phase Transitionmentioning
confidence: 68%
“…Experimentally, some compensation temperature measurements in Fe 3 O 4 and Mn 3 O 4 superlattices [67] and Ni(H-COO) 2 · 2H 2 O [68] were observed. In like manner, previous studies show that at the compensation temperature, the coercivity of a material increases dramatically and at this point, only a small conductor field to invert the sign of the magnetization [64,[69][70][71][72] is required. (J 1 , , T ), (J C , , T ), and (J S , , T ) Planes…”
Section: The Behavior Of the Magnetization Curves: Firstand Second-ormentioning
confidence: 95%